Re-evaluating how to measure jurors’ comprehension and application of jury instructions - Baguley, Chantelle M. (Psychology, crime & law, 2020)
In order for jurors to decide a legally correct verdict, they must comprehend and apply jury instructions. To date, empirical research has focused on jurors’ comprehension of instructions. However, it is difficult to know how well jurors actually comprehend instructions, because the tests currently used by researchers to measure jurors’ comprehension provide different estimates of jurors’ comprehension. It is also difficult to know the degree to which jurors apply instructions, because researchers have not directly examined this question. This article reviews the current tests used to measure jurors’ comprehension of instructions, and the current methods used to make inferences about jurors’ application of instructions. It then critically analyses these approaches, and recommends ways to improve these approaches in future research, to enable researchers to draw more precise conclusions about the quality of jurors’ decision-making.